The Relationship Between Macroeconomic Statistics Guidelines and Accounting Standards - Laliberte, Lucie (IMF Working Papers; Working Paper ;, 2004)
This paper aims to promote harmonization between macroeconomic statistics guidelines and accounting standards. It first highlights recent development that act as drivers to the harmonization of the two systems. It then compares the two systems and reviews approaches aimed at further harmonization. This is followed by a description of the specificity of each system in terms of the emphasis each puts on various aspects of data quality. The paper concludes that through differences between the two systems will remain, they are more likely to be documented, via statistical metadata, than in the past; in the public sector, there is a promising potential for data reconciliation in the form of bridging items; and convergence is likely to be achieved in selected areas.